DYNAMICS OF GROWTH OF ALBIZIA ADIANTHIFOLIA AND ALBIZIA ZYGIA (TWO LOCAL LEGUMINOUS PLANTS WITH RAPID GROWTH) DURING THE REGENERATION OF THE POST-FARMING FALLOW AND DEGRADED SPACES - Henri, Kouassi Kouadio; Hervé, Kouassi Roland; Denis-Esdras, Amon Ano (International Journal of Research -GRANTHAALAYAH, 2018)
The threat which is on the forests and wooded spaces of Africa and particularly those of Côte d'Ivoire is accentuated over the years. The quoted leading causes are the land pressure related to demography, the anarchistic exploitation of the forest woody plants and itinerant agriculture. In many cases, the afforestation is the recommended palliative measure. But with which woody plants does one retimber in Côte d'Ivoire? Which assessment are previous initiatives made? On several occasions the exotic woody plants with rapid growth were used without success. The main objective of this study is to identify local woody plants with rapid growths of which the use will contribute to a significant degree to fast regeneration of our forests, degraded spaces and the post-farming fallow. Floristic inventories and measurements were carried out on the stems of Albizia adianthifolia and Albizia zygia in elementary plots of 400 m ² (20m X 20m). Two local arborescent Leguminous plants with rapid growth were identified for this purpose. They were: Albizia adianthifolia and Albizia zygia. The experiments showed that these species reach the maximas of their growth in height and thickness as from nine (9) years. The sowing of the fallow and/or spaces degraded by these woody species supports the fast regeneration of these degraded spaces.